1977
DOI: 10.1037/0021-843x.86.2.145
|View full text |Cite
|
Sign up to set email alerts
|

Verbal mediation in young aggressive boys.

Abstract: Aggressive and normal boys from 77 to 97 months of age were compared on measures of verbal ability, types of self-guiding speech, nonverbal intelligence, reading achievement, impulsivity, ability to inhibit responses, and response modulation following overt and covert commands. Discriminant function analysis resulted in correct classification of 88% of the cases. Variables with high scores contributing to classification as aggressive included vocabulary, immature and irrelevant private speech, fast reaction ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0
1

Year Published

1982
1982
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(36 citation statements)
references
References 29 publications
3
32
0
1
Order By: Relevance
“…The study provides further indication of substantial differences between male and female aggression: the further being related to external locus of control, the latter not, at least at this particular age. The fact that external locus of control correlated with aggression in boys is further in line with the findings of Camp [1977], who suggested that aggressive boys have a control deficiency, and Rodriguez and Rivera [June 1990], who found self-control techniques to reduce aggressive behaviors in adolescent boys.…”
Section: Discussionsupporting
confidence: 73%
“…The study provides further indication of substantial differences between male and female aggression: the further being related to external locus of control, the latter not, at least at this particular age. The fact that external locus of control correlated with aggression in boys is further in line with the findings of Camp [1977], who suggested that aggressive boys have a control deficiency, and Rodriguez and Rivera [June 1990], who found self-control techniques to reduce aggressive behaviors in adolescent boys.…”
Section: Discussionsupporting
confidence: 73%
“…Teachers should guard against the use of punitive, confrontational, and deprecatory methods because these have been shown to increase the possibility of violent reactions from students (Rock 1992). Students who exhibit violent behavior often do not employ appropriate methods of communicating feelings of anger and use a verbal style that lacks verbal mediation skills (Camp 1977). Instruction in appropriate communication methods in stressful situations should be an essential part of the educational program throughout the school year.…”
Section: Arrangement Of the Learning Environmentmentioning
confidence: 99%
“…h) Análisis sobre el estilo de pensar y de conducirse de niños cognitivamente impulsivos (Douglas et col., 1976;Dickie, 1973). i) La relación entre el lenguaje interiorizado y el estilo conductual en niños agresivos fue analizada por Camp (1977) Borkowski y Cavanaugh (1978). k) En el área de la conducta académica, además del estudio de la resistencia a la tentación, se ha estudiado la demora de la gratificación (Mischel, 1974(Mischel, , 1981(Mischel, , 1981a, la solución de problemas (Stone, Hinds y Schmidt, 1975;Spivack y Shure, 1974, etcétera.…”
Section: Aplicacionesunclassified